2020
DOI: 10.1021/acs.langmuir.0c00511
|View full text |Cite
|
Sign up to set email alerts
|

Vorticity-Aligned Droplet Bands in Sheared Immiscible Polymer Blends Induced by Solid Particles

Abstract: The spatiotemporal organization of complex fluids under flow can be strongly affected by incorporating solid particles. Here, we report that a monolayer of interfacially active microspheres preferentially wetted by the matrix phase can bridge droplets into vorticity-aligned bands in immiscible polymer blends at intermediate particle concentrations and low shear rates. Strong particle bridging ability and the formation of rigid anisotropic droplet bands with a negligible inertia effect in the Newtonian matrix a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 58 publications
1
2
0
Order By: Relevance
“…3c′). A similar phenomenon has also been reported in our previous studies with PS ellipsoids and microspheres [17,38,39] and interpreted by using the Jeffery orbits theory [40] in the framework of fluid mechanics. It is suggested that only when oriented in the vorticity direction can these rigidized droplets rotate around their long axes under slow shear flow with a minimized energy dissipation.…”
Section: Blends Filled With Hydrophobic Rodssupporting
confidence: 87%
“…3c′). A similar phenomenon has also been reported in our previous studies with PS ellipsoids and microspheres [17,38,39] and interpreted by using the Jeffery orbits theory [40] in the framework of fluid mechanics. It is suggested that only when oriented in the vorticity direction can these rigidized droplets rotate around their long axes under slow shear flow with a minimized energy dissipation.…”
Section: Blends Filled With Hydrophobic Rodssupporting
confidence: 87%
“…Of the plethora of anisotropic shear-induced structures observed, a subset feature log-rolling flocs, whose formation strongly depends on the degree of confinement. These vorticity-aligned log-rolling flocculated structures have been observed in emulsions [19]; particleloaded polymer blends [20]; carbon nanotube suspensions [21,22]; carbon black suspensions [23][24][25]; mud samples [26]; and other suspensions of attractive particles [27,28]. A complete understanding of such log-rolling floc formation is crucial for applications where complex fluids might flow through confined geometries (e.g., 3D printing) and for scalable methods of producing anisotropic materials (e.g., films with anisotropic conductivity [29,30]).…”
Section: Introductionmentioning
confidence: 53%
“…Its vast applications are directed to microfluidics, the food industry, and granular materials, among other possibilities. Some band formation studies have been reported in the literature for different types of samples, such as granular materials [1,2], stiff particle suspensions [3,4], liquid crystals [5], polymer solutions [6], in surfactant wormlike micelles [7,8], and attractive emulsions [9,10]. The arrangement of bands in emulsions is reported mainly for the concentric cylinder geometry [11], where band formation can occur in all three directions (the directions of the flow, the velocity gradient, or the direction of vorticity).…”
Section: Introductionmentioning
confidence: 99%